(untitled) (Revista Argentina de Musicología, 2019)
In this paper, we examined three cases taken either from the musicological literature or from our own experience as researchers in which the subject of music and affect was treated in vague or inconsistent ways. To frame each case, we first tracked down definitions of key terms on the subject. Next, we reviewed the relationships between the music-affect dyad and the notion of cognition, the nature-nurture problem, the distinction between discrete and dimensional models of affect, and the notion of music as a multimodal experience. We conclude that vagueness and inconsistencies in the musicological field when dealing with music’s affective impact are problematic, and that might arise either from the poorly understood status of the topic or from approaches that lack the required integration with other disciplines and/or subdisciplines.